Science Policy in Spain: National Programs and Public Perception of Science - Veronica M. Novikova (Vestnik MGIMO-Universiteta, 2016)
The article studies the organization and financing of the Spanish state policy in the field of scientific and technological research and innovation, its institutional basic and the legal and regulatory framework, as well as analyzes the problem of Spanish public opinion on research and work of scientists. The author uses the methods of texts analysis, interviews and expert assessments. First, the author examines the legislative framework of scientific and technical policy of the Kingdom of Spain, the theoretical basis of its development and implementation Then, we study the institutional characteristics of scientific policy in the country, in particular the principal organs of coordination, financing and implementation, including their functional powers. Finally, we investigate the Spanish people perception of the science as a whole, the introduction of new technologies and the sources of material support to scientific research. In conclusion, the past 10years have seen active steps of the Spanish authorities improve the legislation in the field of science in order to ensure the effective implementation of innovation and enhance the overall competitiveness of the country in the international arena. An important finding was also positive changes in the public attitude towards science and the intensification of the dialogue between the scientific community and the public.